2015
DOI: 10.1161/hypertensionaha.115.05344
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epidermal Growth Factor Receptor and Endoplasmic Reticulum Stress in Vascular Remodeling Induced by Angiotensin II

Abstract: The mechanisms by which angiotensin II (AngII) elevates blood pressure and enhances end-organ damage appear to be distinct. However, the signal transduction cascade by which AngII specifically mediates vascular remodeling such as medial hypertrophy and perivascular fibrosis remains incomplete. We have previously shown that AngII-induced epidermal growth factor receptor (EGFR) transactivation is mediated by metalloprotease ADAM17, and that this signaling is required for vascular smooth muscle cell hypertrophy b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
93
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 41 publications
(53 reference statements)
6
93
1
1
Order By: Relevance
“…In line with this, therapies which are known to reduce oxidative stress, such as mineralocorticoid antagonists, or angiotensin-converting enzyme inhibitors, are known to improve vascular stiffness acceleration. 23 One of the key novel mechanisms linking oxidative stress to fibrosis involves small GTPbinding protein dissociation stimulator. Its upregulation by statins results in Rac1 degradation and reduced oxidative stress 24 and may reduce cardiac and possibly vascular fibrosis.…”
mentioning
confidence: 99%
“…In line with this, therapies which are known to reduce oxidative stress, such as mineralocorticoid antagonists, or angiotensin-converting enzyme inhibitors, are known to improve vascular stiffness acceleration. 23 One of the key novel mechanisms linking oxidative stress to fibrosis involves small GTPbinding protein dissociation stimulator. Its upregulation by statins results in Rac1 degradation and reduced oxidative stress 24 and may reduce cardiac and possibly vascular fibrosis.…”
mentioning
confidence: 99%
“…Ang II injection could increase the blood pressure of mice. However, a recent study demonstrated that treatment with EGFR inhibitor erlotinib attenuated Ang II-induced vascular remodeling and cardiac hypertrophy but not hypertension in mice, indicating that the mechanisms by which Ang II elevates blood pressure and enhances end-organ damage may be distinct (Takayanagi et al, 2015). Another independent group found that Ang II-induced hypertrophy in cerebral arterioles involves EGFR signaling, which is independent of blood pressure (Chan et al, 2015).…”
mentioning
confidence: 99%
“…In a study that appeared last year in Hypertension, Eguchi's group reported that inhibiting EGFR or endoplasmic reticulum stress attenuated vascular remodeling and cardiac hypertrophy in mice infused with Ang II, without affecting the increase in blood pressure. 1 In the current issue, these investigators extend these observations further by showing that knockout of ADAM17 specifically in vascular smooth muscle cells prevents cardiac hypertrophy, vascular medial hypertrophy, and perivascular fibrosis in mice treated with Ang II, again without affecting the induced hypertension.…”
Section: See Related Article Pp 949-955mentioning
confidence: 61%
“…In a study that appeared last year in Hypertension, Eguchi's group reported that inhibiting EGFR or endoplasmic reticulum stress attenuated vascular remodeling and cardiac hypertrophy in mice infused with Ang II, without affecting the increase in blood pressure. 1 In the current issue, these investigators extend these observations further by showing that knockout of ADAM17 specifically in vascular smooth muscle cells prevents cardiac hypertrophy, vascular medial hypertrophy, and perivascular fibrosis in mice treated with Ang II, again without affecting the induced hypertension.2 ADAM17 deficiency also diminished EGFR activation and endoplasmic reticulum stress in the vasculature, and a similar outcome was achieved by treatment of Ang II-infused mice with a human cross-reactive ADAM17 inhibitory antibody ( Figure).These new findings are remarkable for several reasons. First, they provide additional support for the contention that increased blood pressure and adverse cardiovascular remodeling, which contributes to end-organ damage, are independent phenomena that can be targeted separately.…”
mentioning
confidence: 99%